(3QSGdI aj GSe GdaGYd gd gh MbjbI aj GdMGd eLGR aj GdeGVjs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3HNW GdeDdas)
(3ChdgG (B:s
(3hHYO aEfc SCdJ Yf GSe GdaGYd gd gh MbjbI aj GdMGd eLGR aj GdeGVj Ch MbjbI aj GdLejY, aGYde Hfj CbQ Gddg Hce GdYjfCf GdLeghQ Ydi Cf GSe GdaGYd MbjbI aj GdMGd Cj MGd JdHS GdaGYd HeYfi GdeTJb efgs
(3BNQgG (B:s
(3hEf bdfG Ef LgGJ GdCaYGd ef GdNdb hGdQRb hGdEMjGA hGdEeGJI hZjQgG MGOKI Ch eJLOOI adjS GdeQGO HMGOKI eYfi GdMOhK GdMbjbj hgh GdhLhO HYO GdYOe Hd GdeQGO HMGOKI eJLOOIs
(3HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdHdGZIs